2012
DOI: 10.1063/1.4731784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapid thermal annealing on GaAs1-xBix alloys

Abstract: Studies on atomic layer deposition Al2O3/In0.53Ga0.47As interface formation mechanism based on air-gap capacitance-voltage method Appl. Phys. Lett. 101, 122102 (2012) A mathematical model for void evolution in silicon by helium implantation and subsequent annealing process J. Appl. Phys. 112, 064302 (2012) Void evolution in silicon under inert and dry oxidizing ambient annealing and the role of a Si1−xGex epilayer cap

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 13 publications
4
50
0
Order By: Relevance
“…As shown in Table 5, for GaAsBi, there is no detectable peak wavelength shift for annealing temperature up to 700 • C and a marginal or no shift for annealing temperature between 700-800 • C. The enhancement of PL intensity at RT is also marginal, up to a maximum of three times, in contrast to the case of dilute GaAsN. Mohmad et al [145] found that the enhancement factor is a constant of 3 for x Bi up to 5% and then decreases to nearly 1 for x Bi = 6.5%. The PL intensity increases with annealing temperature up to 700 • C and then decreases for x Bi = 4% and up to 600 • C for x Bi = 6.5%.…”
Section: Thermal Stability and Bi Diffusionmentioning
confidence: 94%
See 3 more Smart Citations
“…As shown in Table 5, for GaAsBi, there is no detectable peak wavelength shift for annealing temperature up to 700 • C and a marginal or no shift for annealing temperature between 700-800 • C. The enhancement of PL intensity at RT is also marginal, up to a maximum of three times, in contrast to the case of dilute GaAsN. Mohmad et al [145] found that the enhancement factor is a constant of 3 for x Bi up to 5% and then decreases to nearly 1 for x Bi = 6.5%. The PL intensity increases with annealing temperature up to 700 • C and then decreases for x Bi = 4% and up to 600 • C for x Bi = 6.5%.…”
Section: Thermal Stability and Bi Diffusionmentioning
confidence: 94%
“…Unfortunately, the Bi-related localized defects in GaAsBi are hardly reduced by annealing method [150]. Although Moussa et al reported that the PL intensity of GaAsBi enhances about one order of magnitude with an annealing temperature of about 700 • C [148], they suggested that the PL intensity improvement is dominated by the reduction of non-Bi-related defects [145]. Nevertheless, GaAsBi laser diodes [248,249] and LEDs [250] have been realized, suggesting the promising application of dilute bismides on optoelectronic devices.…”
Section: Photoluminescence Intensitymentioning
confidence: 97%
See 2 more Smart Citations
“…The incorporation of Bi has been shown to have a dramatic impact on the band structure of GaAs. A band gap reduction of around 90 meV per percent of Bi and a large increase of spin-orbit (SO) split-off energy have been observed [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This increase of spin-orbit interaction could suppress the non-radiative Auger recombination processes that affect the efficiency of lasers in the near infrared; it is also very attractive for semiconductor spintronics.…”
Section: Iintroductionmentioning
confidence: 99%